2019
DOI: 10.1108/aaaj-02-2017-2860
|View full text |Cite
|
Sign up to set email alerts
|

The role of accounting in mediating empathic care for the “other”

Abstract: Purpose This paper hypothesizes that a system of accounting underpinned by attributions of harm has the capacity, more than conventional accounting, to elicit empathic concern among managers, by becoming the mediating link between organisational responsibility and concern for the “other”. Design/methodology/approach The literature-inspired reflections presented in this paper stem from the theoretical perspective of care-ethics supported by the notions of empathy and proximity to highlight how the propensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…, 2001) to a large extent resulted in it being left up to organisations to define workplace norms and appropriate behavioural patterns. The study has demonstrated how the #MeToo movement has mobilised and routinised the continuous virtual and physical presence of “the Other” in the lives of organisational and individual actors (Butler, 2005; Dellaportas, 2019; Roberts, 2009). The intensity of citizens' demands for accountability highlighted the unhealthy behavioural patterns and imbalances for which organisations and individuals in power required to be called to account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2001) to a large extent resulted in it being left up to organisations to define workplace norms and appropriate behavioural patterns. The study has demonstrated how the #MeToo movement has mobilised and routinised the continuous virtual and physical presence of “the Other” in the lives of organisational and individual actors (Butler, 2005; Dellaportas, 2019; Roberts, 2009). The intensity of citizens' demands for accountability highlighted the unhealthy behavioural patterns and imbalances for which organisations and individuals in power required to be called to account.…”
Section: Discussionmentioning
confidence: 99%
“…"The Other" is also complex. Understood as a wide assembly of stakeholders gathered in accountability forums (Dellaportas, 2019;Goncharenko, 2021;Yates et al, 2020), "the Other" is contra-lateral to an accountable actor. One may wonder what is happening on the side of "the Other".…”
Section: Introductionmentioning
confidence: 99%
“…If those concerned with contested markets demand organizational information as a potential means to reduce their fears, and the type and level of accountability is discretionary on the part of organizational entrepreneurs, the market is not likely to succeed. This stems from the very nature of accountability and the need for an accountable individual to identify and reflect on their own behavior against some ideal (Roberts, 2009), and feel a sense of moral obligation toward the public interest or the social good regarding their behavior (Schweiker, 1993; Lovell, 1995; Shearer, 2002; Lehman, 2005; Dellaportas, 2019; Frey-Heger and Barrett, 2021). Contested-market operators are morally opposed to the inequitable operating constraints they often face for the opportunity to conduct legal market activities (Romi et al , 2021).…”
Section: Trust Transparency and Accountability In Contested Marketsmentioning
confidence: 99%
“…2. While prior accounting literature has not specifically focused on “vulnerable populations” in contested markets, with few exceptions mentioned throughout this paper, much research has examined the role of accounting in protecting various populations facing inequities. The vulnerable then are defined as a moral obligation of one who can meet the needs of those in need (Dellaportas, 2019). For example, victims of natural disasters (Baker, 2014; Lai et al , 2014; Sargiacomo, 2014), those facing economic inequality (Tweedie and Hazelton, 2019), individuals displaced by climate change (Perkiss and Moerman, 2018), people of color (Annisette, 2003; Hammond and Streeter, 1994), the homeless (Cooper et al , 2016) and women (Broadbent, 1998; Haynes, 2017; Lehman, 2019), among many others.…”
Section: Notesmentioning
confidence: 99%
“…In a short space of time, auditors are required to gain the trust of workers, overcome language, culture and sometimes gender divides, and identify potentially hidden situations of exploitation. Yet, as Dellaportas explains, despite the precise and regimented nature of social auditing which derives from the accounting professional, "One unfortunate side-effect of accounting as a procedural technology is its capacity to deny the social aspects of business activities when accounting processes are separated from its social framework" because it "diminishes a manager's ethical ideal by disconnecting managers from the effects of organizational practice when accounting dwells predominantly on technical matters and organizational performance rather than organizational impacts" [23]. As a result, auditors' accounting training and focus on procedures can hinder the social aspects that are necessary to effectively conduct worker interviews, such as trust, that can lead to the reporting of situations of exploitation.…”
Section: Social Compliance Auditsmentioning
confidence: 99%